2020
DOI: 10.1159/000506134
|View full text |Cite
|
Sign up to set email alerts
|

Effortful Control – A Transdiagnostic Dimension Underlying Internalizing and Externalizing Psychopathology

Abstract: Effortful control (EC) or self-regulation refers to the ability to regulate behavior, emotion, and cognition. It has been identified as a contributor to both adaptive and adverse outcomes in children, adolescents, and adults and this across many domains. As such, it could be considered as a transdiagnostic dimension underlying internalizing (e.g., mood and anxiety disorders) and externalizing (e.g., substance use disorders, ADHD) psychopathology. We aimed to examine the role of EC throughout the adult psychopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 94 publications
5
30
0
Order By: Relevance
“…Children and adolescents who experience abuse or other forms of traumatic victimization, and adults with histories of childhood victimization, have been shown to exhibit either (or both) a cognitive/ attentional preoccupation with, or avoidance of, awareness of potential threats (Bardeen et al, 2020;McLaughlin et al, 2020;Terpou et al, 2019;Weissman et al, 2020b). Consistent with this cognitive bias, traumatically victimized or neglected children and youth also often experience impairment in executive functions and effortful control that can lead to behavioral disinhibition and impulsivity (e.g., reckless, self-harming, or dysfunctional self-soothing behavior) or difficulty initiating and completing normative goal-directed behavior (e.g., academic problems or failure, isolation or rejection in peer relationships) (Beauchaine & Cicchetti, 2019;El-Sheikh et al, 2009;Hankin et al, 2017;Huang-Pollock et al, 2017;Oshri et al, 2018;Santens et al, 2020;Snyder et al, 2019;Wade et al, 2020;Zhu et al, 2016).…”
Section: Criteria For Developmental Trauma Disordermentioning
confidence: 99%
“…Children and adolescents who experience abuse or other forms of traumatic victimization, and adults with histories of childhood victimization, have been shown to exhibit either (or both) a cognitive/ attentional preoccupation with, or avoidance of, awareness of potential threats (Bardeen et al, 2020;McLaughlin et al, 2020;Terpou et al, 2019;Weissman et al, 2020b). Consistent with this cognitive bias, traumatically victimized or neglected children and youth also often experience impairment in executive functions and effortful control that can lead to behavioral disinhibition and impulsivity (e.g., reckless, self-harming, or dysfunctional self-soothing behavior) or difficulty initiating and completing normative goal-directed behavior (e.g., academic problems or failure, isolation or rejection in peer relationships) (Beauchaine & Cicchetti, 2019;El-Sheikh et al, 2009;Hankin et al, 2017;Huang-Pollock et al, 2017;Oshri et al, 2018;Santens et al, 2020;Snyder et al, 2019;Wade et al, 2020;Zhu et al, 2016).…”
Section: Criteria For Developmental Trauma Disordermentioning
confidence: 99%
“…Importantly, effortful control is thought to develop within the first year of life and becomes more refined with the maturation of the executive attention network throughout early childhood, late childhood, adolescence, and young adulthood (Rueda et al, 2012). In a recent review, Santens et al (2020) found that effortful control was related to many forms of internalizing and externalizing psychopathology but highlighted that the necessity of future investigations regarding different facets of effortful control (e.g., activation control, inhibitory control) and their relation to emotion processing.…”
Section: Effortful Controlmentioning
confidence: 99%
“…Indeed, self-regulation is an early ability to exert control over cognition, behavior and emotions, especially negative ones, and does not appear to confer specific risk for single disorders but rather to present general risk for multiple disorders. The inadequate development of this ability may become a transdiagnostic risk factor for the appearance of psychiatric disorders [ 43 , 44 ], thereby having an impact on social adaptation throughout development [ 45 , 46 , 47 ]. Bradley [ 40 ] also presented a model in which affect dysregulation is a core factor in different types of psychopathologies, calling it a “general arousal factor”.…”
Section: Introductionmentioning
confidence: 99%